The Law librarian in the state of Sao Paulo: a comparative study - Akama dos Reis, Daniela Majorie [UNESP]; Sales Catarino, Paula Drumond (Univ Brasilia, Dept Ciencia Informacao, 2020)
This article deals with the concepts of the librarian as a professional and his specialty in the legal area. Statistical data will be presented about these professionals from the state of Sao Paulo, and a comparison is made with previous study data. We focus on the law library professionals, their routines and services, and the difficulties in their professional path. The results show the diversity of profiles and services offered by the Sao Paulo law librarians.
Keywords: Law library; Professional profile; Law librarian